2016
DOI: 10.1103/physrevb.93.024110
|View full text |Cite
|
Sign up to set email alerts
|

Structural, vibrational, and electrical study of compressed BiTeBr

Abstract: Compresed BiTeBr has been studied from a joint experimental and theoretical perspective. Room-temperature x-ray diffraction, Raman scattering, and transport measurements at high pressures have been performed in this layered semiconductor and interpreted with the help of ab initio calculations. A reversible first-order phase transition has been observed above 6-7 GPa, but changes in structural, vibrational, and electrical properties have also been noted near 2 GPa. Structural and vibrational changes are likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 61 publications
7
39
1
Order By: Relevance
“…An analysis of BiTeBr and BiTeCl shows the absence of TPT in these compounds. In BiTeBr, a CPT occurs before the TPT that precludes the latter that is in agreement with results of [28]. In BiTeCl, the topological phase does not appear due to a relatively large band gap at zero pressure.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…An analysis of BiTeBr and BiTeCl shows the absence of TPT in these compounds. In BiTeBr, a CPT occurs before the TPT that precludes the latter that is in agreement with results of [28]. In BiTeCl, the topological phase does not appear due to a relatively large band gap at zero pressure.…”
Section: Introductionsupporting
confidence: 89%
“…It was also shown that this hexagonal-orthorhombic CPT occurs at a pressure of ∼6GPa [24]. For the BiTeBr compound, the CPT has been experimentally observed at similar pressures (6-7 GPa) [28].…”
Section: Introductionmentioning
confidence: 68%
“…Therefore, the geometric optimization process is performed to detect that the structure is the correct structure. The lattice parameters obtained as a result of optimization are given in Table 1 [29,30,[33][34][35][36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…Such a low value is a good indicator for an adequate convergence of the calculations. [30][31][32][33][34][35][36][37][38][39]. The atomic positions belonging to these compounds are given in Table 1.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…For completeness, the experimental and theoretical pressure dependence of the axial ratios of 41,84 because the minimum of the c/a ratio can be originated by a change in the ratio of interlayer/intralayer forces, and it cannot be taken for granted that this change should be necessarily translated into a change in the electronic density of states near the Fermi level.…”
Section: Hp-xrd Measurementsmentioning
confidence: 99%